Penerapan Prinsip Transparansi Dalam Tata Kelola Pasar Tradisional Dan Pasar Modern Di Kabupaten Pemalang - Zahro, Aula Fatania; Kurniasih, Denok; Tobirin, Tobirin (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Markets have an important role as a means of fulfilling community needs and also the economic welfare of a region. The government is responsible for authorizing the existence of markets, both traditional markets and modern markets. The aim of this research is to determine the transparency of traditional market and modern market governance policies in Pemalang Regency. This research uses a qualitative descriptive research method with a case study approach and the data required is primary and secondary data obtained through observation, interviews and documentation. The results of this research use the transparency dimension which shows that there is openness of the Pemalang Regency regional government in determining governance policies in traditional markets and modern markets in Pemalang Regency. The inhibiting factors in implementing this policy are communication between regional governments and third parties, cooperation partners, and inaccuracies in regional government strategies.